Challenges in diagnosis and management of snake bites in resource poor settings: A case report of suspected Russell’s viper envenomation - Lamb, Thomas (Indian Journal of Case Reports, 2015)
Snake bite is a common and neglected problem resulting in a large global mortality and morbidity per year. In India alone, an estimated 45,900 deaths occur per annum. The outlined case of suspected Russell’s Viper (Daboia russelii) envenomation occurred in rural West Bengal. The case was misdiagnosed on two occasions resulting in a substantial delay in antivenom therapy. The resultant delay contributed to a significant morbidity and prolonged hospital admission. The case report illustrates some practical difficulties faced by clinicians pertaining to diagnosis, complications and resource limitations. These areas are discussed with a view to improving awareness and management. Simple practical tools are included to assist a clinician faced with snake bites in South Asia.